ASPEN HYSYS SIMULATION FOR LPG PRODUCTION OPTIMIZATION IN DEETHANIZER COLUMN: CASE STUDY IN DELAYED COKING UNIT - Agatha Sekar Windyaningrum; Arif Nurrahman; Pusparatu Pusparatu; Asa Aditya Persada; Raihan Fakhri (Testing Center for Oil and Gas LEMIGAS, 2025)
The global petroleum refining industry faces increasing pressure to optimize resource utilization while ensuring environmental sustainability. This challenge is further intensified by the rising demand for lighter, cleaner fuels and heavier crude oil feedstocks. The Delayed Coking Unit (DCU) plays an important role in refining processes by converting vacuum residue into valuable products such as Liquefied Petroleum Gas (LPG), diesel, naphtha, and green coke. The LPG market, currently valued at 113.7 billion, is projected to grow to 165.1 billion by 2033. Within this process, the deethanizer column utilizes pressurized distillation to separate ethane (C2) from LPG. According to evaluation results, the column's feed flow was recorded at 83.7 tons per day, with a feed temperature of 102.61°C and a top column pressure of 18.84 kg/cm². The feed composition data was obtained through laboratory analysis. According to the calculation, the theoretical tray number was 17, the reflux ratio was 0.9936, and the total tray efficiency was 56.57%. The optimization of deethanizer column operating conditions was carried out by increasing the bottom product yield, which aimed to determine the optimum point with the greatest LPG yield. Based on a trial-and-error using Aspen Hysys V14 software, the optimum conditions were identified when the column was operated at 110℃ reboiler temperature and reflux ratio 2, which could increase LPG yield to 73.21 tons/day with 98.1% w/w purity. Economically, the profit increased from 18,444,932.92/year to 22,640,582.13/year